Challenges HR Managers Facing due to COVID-19 and Overcoming Strategies: Perspectives from Georgia - Gigauri, Iza (Archives of Business Research, 2020)
Purpose - The paper aims to clarify the implications of COVID-19 on organizations and Human Resource Management. The study proposes organizational responses to the pandemic, and outlines how to adapt HRM practices to the new normal. It aims to explore how human resource managers support employees and whether top management has a strategic focus on employee wellbeing during the crisis. Design/methodology/approach - The paper opted for quantitative research method using descriptive research design. The data was collected with the survey. Questionnaires were distributed to the HR managers through the Internet. The response rate is 32%. The gathered data was analyzed through SPSS. Findings - The research provides empirical insights on the challenges organizations are facing due to the pandemic. It sheds light on the decisions Georgian managers took in times of Covid-19. The paper suggests that changes in HR policies will lead to successfully overcome emerged difficulties with remote working, flexible schedule, and employee wellbeing. Research limitations/implications - The research results may lack generalizability due to the small amount of participants in the survey. Therefore, researchers are encouraged to conduct future larger-scale research. Practical implications - The paper includes implications for the development of HRM strategy to adapt to the new reality shaped by the pandemic, and for managing remote working systems considering the employee perspectives. Social implications - The paper contributes to decisions of policymakers and governments regarding the workforce, and to the society for responding the changes. Originality/value - This paper studied the role of HR managers in employee adaptation to the pandemic state, their perceptions towards organizational response to the crisis, and supportive behavior.